ROCK MAGNETIC RECORD OF THE LAST GLACIAL-INTERGLACIAL CYCLE FROM THE KURTAK LOESS SECTION, SOUTHERN SIBERIA - Zhu R.X.; Sun J.M.; Matasova G.; Kazansky A.; Zykina V. (My University, 2003)
Detailed rock magnetic investigations, grain size determination and X-ray diffraction were carried out on loess and buried soils of the last glacial-interglacial cycle from Kurtak, southern Siberia. The susceptibility and the sand fraction of >63 mum fluctuate in parallel, suggesting that the higher susceptibility values in the loess horizons are mainly associated with the coarse size fraction. The frequency dependence of the magnetic susceptibility of the loess and buried soils is very low and uniform, indicating the absence of superparamagnetic grains and negligible pedogenically induced enhancement of magnetic susceptibility. The magnetic assemblage is dominated by multidomain-like magnetite grains. Maghemite and haematite are also present in the buried soils and loess horizons. Goethite may have been formed from gleying or waterlogging processes under a cooler and more humid climate. The coarse magnetite grains, which contribute significantly to magnetic susceptibility, are probably carried by valley winds and derived from local sources. Thus, the coarser magnetite grains with higher susceptibility values in the loess horizons could mainly reflect stronger wind intensity during cold and semi-arid conditions, and the consequent ease with which dense magnetite particles can be transported. The lower susceptibility values in the buried soil horizons are mainly caused by weaker wind intensity during interglacial and interstadial periods, although post-depositional processes associated with gleying modifications are also partially responsible for the observations.
Keywords: buried soil; loess; palaeoclimate; rock magnetism; Siberia